LasΔ5315 Effector Induces Extreme Starch Accumulation and Chlorosis as Ca. Liberibacter asiaticus Infection in Nicotiana benthamiana - Pitino, Marco; Allen, Victoria; Duan, Yongping (Frontiers in Plant Science, 2018)
Huanglongbing (HLB), a destructive plant bacterial disease, severely impedes worldwide citrus production. HLB is associated with a phloem-limited α-proteobacterium, Candidatus Liberibacter asiaticus (Las). Las infection causes yellow shoots and blotchy mottle on leaves and is associated with excessive starch accumulation. However, the mechanisms underlying the starch accumulation remain unknown. We previously showed that the Las5315mp effector induced callose deposition and cell death in Nicotiana benthamiana. In this study, we demonstrated that Las can experimentally infect N. benthamiana via dodder transmission. Furthermore, we revealed another key function of the Las5315 effector by demonstrating that transient expression of the truncated form of the effector, LasΔ5315, induced excessive starch accumulation by 6 fold after 8 dpi in N. benthamiana after removal of the chloroplast transit peptide from the Las5315mp. The induction mechanisms of LasΔ5315 in N. benthamiana were attributed to the up-regulation of ADP-glucose pyrophosphorylase, granule-bound starch synthase, soluble starch synthase, and starch branching enzyme for increasing starch production, and to the significant down-regulation of the starch degradation enzymes: alpha-glucosidase, alpha-amylase, and glycosyl hydrolase for decreasing starch degradation. This is the first report that Las can infect the model plant N. benthamiana. Using this model plant, we demonstrated that the LasΔ5315 effector caused the most prominent HLB symptoms, starch accumulation and chlorosis as Las infection in N. benthamiana. Altogether the Las 5315 effector is critical for Las pathogenesis, and therefore, an important target for interference.